Etika Pelayanan Publik Pada Kantor Dinas Kependudukan Dan Catatan Sipil Kota Makassar - Nurfaidah, Sulastri; Usman, Jaelan; Hawing, Hardianto (Universitas Muhammadiyah Makassar, 2025)
The results of this research show that Service Ethics at the Makassar City Population and Civil Registry Office in terms of the services provided to the community have been said to be effective, accurate and of high quality, where the population registration process, issuance of identity documents such as KTPs and birth certificates, as well as other services have met community administrative needs quickly and accurately. The services provided by the Makassar Civil Registry Office are designed to be efficient and also save time for the public. Then the public services established at the Makassar City Population and Civil Registry Office have similarities in the process of processing documents such as Digital KTPs, Family Cards, birth certificates, and so on. The process generally involves gathering the required information and documents, verifying the data, and printing the requested documents.